A Critique on the Book Historical Origin of Qajar Tribe - Mohsen Rahmati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Qajar dynasty, which seized political power in Iran at the beginning of the thirteenth century AH, had a tribal origin, but despite extensive research, its origins remain unclear. Clarification of this tribal origin can help to better understand the issues of Qajar history, and the book "Historical Origin of the Qajar Tribe" has been written for this purpose. Since the study and explanation of this historical origin from three perspectives of ethnic genealogy can be explained, the evolution of the identity and endeavors of the tribe during the centuries, and the study of the historical conditions, and the leaders of this tribe were changed to a king of Iran during this period, the question is, which perspective that the author has explained the origin of the Qajar tribe through has been able to clarify the origin of the Qajar tribe. This study shows that the author of this work combines the first two fields and despite the importance of the subject and the multiplicity of sources, which is one of the advantages of the book, due to methodological, literary, and content errors in neither of the above two areas, he has not able to clarify the origin of the Qajars.